What attachment to peace? Exploring the normative and material dimensions of local ownership in peacebuilding. Issue 5 (29th March 2016) - Lemay-Hébert, Nicolas; Kappler, Stefanie
Abstract: The peacebuilding and academic communities are divided over the issue of local ownership between problem-solvers who believe that local ownership can 'save liberal peacebuilding' and critical voices claiming that local ownership is purely a rhetorical device to hide the same dynamics of intervention used in more 'assertive' interventions. The article challenges these two sets of assumptions to suggest that one has to combine an analysis of the material and normative components of ownership to understand the complex ways in which societies relate to the peace that is being created. Building on the recent scholarship on 'attachment', we claim that different modalities of peacebuilding lead to different types of social 'attachment' – social-normative and social-material – to the peace being created on the part of its subjects.